Adsorption of Cd(II) in water by mesoporous ceramic functional nanomaterials. Issue 4 (17th April 2019) - Xue, Zhongjun; Liu, Na; Hu, Hongxiang; Huang, Jieying; Kalkhajeh, Yusef Kianpoor; Wu, Xiuyuan; Xu, Nian; Fu, Xiaofei; Zhan, Linchuan
Abstract : Mesoporous ceramic functional nanomaterials (MCFN) is a self-assembled environmental adsorbent with a monolayer molecular which is widely used in the treatment of industrial wastewater and contaminated soil. This work aimed to study the relationship between the adsorption behaviour of Cd(II) by MCFN and contact time, initial concentration, MCFN dosage, pH, oscillation rate and temperature through a batch adsorption method. The adsorption kinetic and isotherm behaviours were well described by the pseudo-second-order and Langmuir models. The batch characterization technique revealed that MCFN had several oxygen-containing functional groups. Using Langmuir model, the maximum adsorption capacity of MCFN for Cd(II) was 97.09 mg g −1 at pH 6, 25°C, dosage of 0.2 g and contact time of 180 min. Thermodynamic study indicated that the present adsorption process was feasible, spontaneous and exothermic at the temperature range of 25–55°C. The results of this study provide an important enlightenment for Cd removal or preconcentration of porous ceramic nanomaterial adsorbents for environmental applications.